Counterfactual thinking affects the excitability of the motor cortex. (April 2015) - Vicario, Carmelo M.; Rafal, Robert D.; Avenanti, Alessio
Abstract: Evidence suggests that monetary reward and affective experiences induce activity in the cortical motor system. Nevertheless, it is unclear whether counterfactual thinking related to wrong choices that lead to monetary loss and regret affects motor excitability. Using transcranial magnetic stimulation (TMS) of the motor cortex, we measured corticospinal excitability of 2 groups of healthy humans asked to actively guess the winning key among two possible alternatives (choice group); or passively assist to monetary outcomes randomly selected by the computer program (follow group). Results document a selective increment of the corticospinal excitability when a monetary loss outcome followed the key selection (i.e., in the choice group). On the other hand, no change in corticospinal excitability was found when participants passively assisted to a monetary loss randomly selected by the computer program (i.e., follow group). These findings suggest that counterfactual thinking and the negative emotional experiences arising from choices causing monetary loss – i.e., "I would have won instead of lost money if I'd made a different choice" – are mapped in the motor system.